Ectopic pregnancy in Conakry, Guinea - Thonneau Patrick; Hijazi Yolande; Goyaux Nathalie; Calvez Thierry; Keita Namory (The World Health Organization, 2002)
OBJECTIVE: To assess the incidence of ectopic pregnancy (EP) in hospitals in Conakry, the capital of Guinea, West Africa. Data on EP incidence in developing countries are rare and often out of date, particularly in Africa. METHODS: A retrospective study was carried out, examining all cases of EP registered in the medical files of two referral maternity units at the Donka and Ignace Deen university hospitals between 1995 and 1999. FINDINGS: The EP incidence at the two maternity units increased from 0.41% to 1.5% of annual deliveries over this period. Haemoperitoneum was observed in most women, with tubal rupture in 93%; only 6 women received conservative treatment. CONCLUSION: The results suggest that the hospital-based incidence of EP per delivery has increased over the last decade in this West African capital, and that health professionals and public health officials in developing countries, especially those in Africa, should consider EP as a major obstetric problem for maternal morbidity.